Controle jurisdicional de políticas públicas: aplicação do princípio da proporcionalidade como critério definidor de limites - Bezerra, Pedro Ivo Soares (2012)
The fundamental rights require effective, especially in the era of normative principles of hierarchy and the supremacy of constitutional provisions. In the democratic state of law, are defined in the constitution and other legislative documents infra, guidelines to be implemented from the adoption of public policies, which serve as instruments to achieve the state goals, which, in brief summary should be directed for the common good. The proposal is to analyze the jurisdictional control over public policy, observing the clash between the need for realization of fundamental rights, especially those who serve to ensure the implementation of the existential minimum, and the obligation to uphold the principles of harmonic division of state functions, the legitimacy democratic as well as the limitations resulting from the reserve for microview of the judiciary. To resolve this conflict between the constitutional principles, it is imperative that the principle of proportionality as a way of enabling the exercise of jurisdictional control over public policies, to promote a heightened role of the judiciary nor that fail to enforce constitutional rights due to the inertia of the State in carrying out public policy.